The foundling - Leary, Ann (MarySue Rucci Books/Scribner, an imprint of Simon & Schuster, 2022)
"It's 1927 and eighteen-year-old Mary Engle is hired to work as a secretary at a remote but scenic institution for mentally disabled women called the Nettleton State Village for Feebleminded Women of Childbearing Age. She's immediately in awe of her employer--brilliant, genteel Dr. Agnes Vogel. Dr. Vogel had been the only woman in her class in medical school. As a young psychiatrist she was an outspoken crusader for women's suffrage. Now, at age forty, Dr. Vogel runs one of the largest and most self-sufficient public asylums for women in the country. Mary deeply admires how dedicated the doctor is to the poor and vulnerable women under her care. Soon after she's hired, Mary learns that a girl from her childhood orphanage is one of the inmates. Mary remembers Lillian as a beautiful free spirit with a sometimes-tempestuous side. Could she be mentally disabled? When Lillian begs Mary to help her escape, alleging the asylum is not what it seems, Mary is faced with a terrible choice. Should she trust her troubled friend with whom she shares a dark childhood secret? Mary's decision triggers a hair-raising sequence of events with life-altering consequences for all"--